Interactions in the (Pre)metastatic Niche Support Metastasis Formation - Doglioni, Ginevra (Front Oncol, 2019)
Metastasis formation is the leading cause of death in cancer patients. Thus, understanding and targeting this process is an unmet need. Crucial steps during the establishment of metastases include the (pre)metastatic niche formation. This process relies on the interaction of the primary tumor with the environment of distant organs (premetastatic niche) and the interaction of cancer cells with their environment when arriving in a distant organ (metastatic niche). Here, we summarize the current knowledge on the interactions in the tumor environment that result in (pre)metastatic niche formation, specifically in the context of tumor secreted factors, extracellular matrix, immune as well as stromal cells, and nutrient availability. We further highlight strategies to disrupt these interactions as therapeutic interventions against metastases.